Sierralta Ríos, Aníbal. El comercio internacional y su impacto en la cultura y el derecho - Almeida Pérez, Mariced Morayma; Vergaray Castillo, Daniela Carolina (Universidad ESAN, 2020)
Currently, international trade is one of the economic activities more outstanding. It does not imply - as the author states - only transfers of goods or services; It also includes a series of elements, among which culture, technology and legal systems are included. For this reason, the international trade has direct effects, through cultural penetration or political interference, both in transnational corporations and in Recipient states and their populations. Sierralta, taking into account these new elements that are affected by economic activity, proposes a new theory: the evolutionary theory of international trade. This is raised not only as a theoretical approach, but also as the development of interdependence between the actors and the time factor in trade.

Actualmente, el comercio internacional es una de las actividades económicas más descollantes. No implica —como expone el autor— solo transferencias de bienes o servicios; comprende, además, una serie de elementos, entre los que se incluyen la cultura, la tecnología y los sistemas jurídicos. Por esta razón, el comercio internacional tiene efectos directos, mediante la penetración cultural o la interferencia política, tanto en las empresas transnacionales como en los Estados receptores y su población. Sierralta, teniendo en cuenta estos nuevos elementos que se ven afectados por la actividad económica, propone una nueva teoría: la teoría evolutiva del comercio internacional. Esta se plantea no solo como un enfoque teórico, sino también como el desarrollo de la interdependencia entre los actores y el factor tiempo en el comercio.
Keywords: International trade; Culture; Comercio internacional; Cultura; Law; Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01